Challenges and recommendations for the UK drug treatment system: findings from a UK expert meeting. (April 2015) - Dar, Karim; Ashby, Fleur; Dhandayudham, Arun; Faizal, Mohammad; Glasper, Anthony; Horsburgh, Tim; Radley, Gaynor; Alam, Farrukh
Abstract In an increasing number of countries, the UK among them, policy and practice in the treatment of drug dependence is evolving from harm reduction towards a greater emphasis on recovery. The UK Drug Strategy reflects this change and guidance on achieving the objectives of the strategy has been provided by the Recovery-Orientated Drug Treatment (RODT) working group. A meeting of eight UK drug-dependence experts was convened in September 2012 with the aim of providing insights into the current status of treatment for opioid dependence in the UK in the context of these policy changes and to discuss possible future developments. The expert group identified several opportunities where the gap between aspirations for drug treatment services and the current reality could be bridged. Key recommendations made by the expert group included: an agreed definition of recovery; a common framework for treatment commissioning based on evidence-based treatment approaches; integration of service delivery with the commissioning framework; integration between organisations to ensure optimal access to treatment and effective use of all treatment/support options; and a focus on outcomes using existing tools for monitoring drug-treatment outcomes. The recommendations made here have implications for all countries placing greater emphasis on recovery.